2006
DOI: 10.1016/j.joca.2006.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Placement of intra-articular injection verified by the backflow technique

Abstract: The backflow technique allows to accurate the intra-articular placement of the needle for "dry" knee joints injection. This technique can be proposed as a learning tool as well as a daily practice technique to ascertaining intra-articular knee injections without using fluoroscopy with injection of contrast material. Further studies are needed to assess the technique for other joint injections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 10 publications
0
35
0
3
Order By: Relevance
“…The study found that the injector's experience influenced the accuracy rate of blinded injections at the SLP site; accuracy rate of 55% (95% CI 34–74) for the less experienced injector compared to 100% (95% CI 81–100) for the more experienced injector [36]. Luc et al [32], however, in their trial of 33 knee injections reported a similar accuracy for blinded injections at the SLP site for a clinical fellow (96%) and experienced rheumatologist (100%). Two other publications that included “unknown” sites of blinded knee injections found similar accuracy irrespective of the level of experience, seniority, and training [2,4].…”
Section: Between-study Analysesmentioning
confidence: 98%
See 1 more Smart Citation
“…The study found that the injector's experience influenced the accuracy rate of blinded injections at the SLP site; accuracy rate of 55% (95% CI 34–74) for the less experienced injector compared to 100% (95% CI 81–100) for the more experienced injector [36]. Luc et al [32], however, in their trial of 33 knee injections reported a similar accuracy for blinded injections at the SLP site for a clinical fellow (96%) and experienced rheumatologist (100%). Two other publications that included “unknown” sites of blinded knee injections found similar accuracy irrespective of the level of experience, seniority, and training [2,4].…”
Section: Between-study Analysesmentioning
confidence: 98%
“…Cunnington et al [2] reported 91% accuracy when a research fellow performed the injections using sonographic-guidance while Luc et al [32] reported 100% accuracy when a medical fellow used “backflow of injected fluid” during IAKIs to confirm intra-articular placement of needles.…”
Section: Between-study Analysesmentioning
confidence: 99%
“…When all approaches are taken together, total accuracy of palpation-guided knee joint injections in the clinical setting has ranged from 40% to 100% (4,9,15,18,36,38,41,56,99). This complicates comparison between studies using different approaches or variations of these approaches.…”
Section: Knee Structuresmentioning
confidence: 99%
“…A majority of the studies (49/57 (86%))6 7 9 11–13 15 17–25 27–30 32–51 53–61 evaluated injections in a single joint, whereas 14% (8/57)5 8 10 16 26 31 52 55 assessed injections in more than one joint. Thirty-five per cent (20/57) of the studies evaluated knee injections,8–10 13 15 16 19–23 26 31 32 36 37 48 52 56 57 46% (26/57) evaluated glenohumeral (GH) joint injections,5 7 8 10 11 15–17 24–26 28 29 31 38–40 42 43 46 47 49 52 54 60 61 21% (12/57) evaluated hip injections8 12 27 30 33 35 41 44 45 50 52 59 62 and 4% (2/57) evaluated sacroiliac (SI) joint injections 18 34. Four studies (7%) assessed injections in the ‘shoulder’, but did not specify which shoulder structure or joint they were injecting 6 53 55 58…”
Section: Resultsmentioning
confidence: 99%
“…The level of evidence for a majority of the studies evaluating major joint USGI accuracy (15/23 (65%))5 8 9 15 16 18 20 21 23 27 30 32 34 36–39 41 42 44–46 49 or LMGI accuracy (28/28 (100%))5 7 9–13 17 19 21–26 28 31 32 36–38 40 43 47 48 50 60 61 were level 1 or 2. The mean accuracy of GH, hip and knee joint USGIs in studies with level 1 or 2 evidence ranged from 91% to 100%,5 8 9 15 18 21 23 32 36–39 42 46 49 whereas the mean accuracy of LMGIs were between 64% and 81% 5 7 9–13 17 19 21–26 28 31 32 36–38 40 43 47 48 50 60 61. These findings provide strong evidence that USGIs in the GH, hip and knee joints are more accurate than LMGIs.…”
Section: Resultsmentioning
confidence: 99%